Peran Guru Kristen Sebagai Fasilitator dalam Menjelaskan Pembelajaran Bermakna bagi Siswa [The Role of Christian Teachers as Facilitators in Explaining Meaningful Learning for Students] - Munte, Imelda Suwati Agnes; Chrismastianto, Imanuel Adhitya Wulanata (Universitas Pelita Harapan, 2024)
Current Christian education has not been optimal in bringing students to the knowledge of God. Teachers only focus on delivering material so that knowledge stops in the cognitive domain and students do not understand the meaning and purpose of the lesson. The solution is teachers need to present meaningful learning for students. The purpose of this paper is to determine the role of Christian teachers as facilitators in developing meaningful learning for students. The method used is a literature review. Meaningful learning is a learning process that can bring students to the highest meaning of learning, namely God's truth. Epistemology is the philosophical view that bridges the highest source of knowledge, the God's truth. The role of Christian teachers as facilitators in meaningful learning is to facilitate students to gain knowledge of God so that students' lives refer to Christian values. It can be concluded that the role of Christian teachers is important in developing meaningful learning for students so that students continue to grow in the God’s truth and glorify God in their lives. The suggestion for next researchers is to deepen about the application of the role of Christian teachers as facilitators in developing meaningful learning through direct observation and enriching reference sources. BAHASA INDONESIA ABSTRACTPendidikan Kristen saat ini belum maksimal dalam membawa murid-murid kepada pengenalan akan Tuhan. Guru hanya berfokus pada penyampaian materi sehingga pengetahuan berhenti pada ranah kognitif dan siswa tidak mengerti makna dan tujuan dari pelajaran tersebut. Solusinya adalah guru perlu menyajikan pembelajaran yang bermakna bagi siswa. Tujuan dari tulisan ini adalah untuk mengetahui peran guru Kristen sebagai fasilitator dalam mengembangkan pembelajaran yang bermakna bagi siswa. Metode yang digunakan adalah studi literatur. Pembelajaran yang bermakna adalah proses pembelajaran yang dapat membawa siswa menemukan makna tertinggi dari pembelajaran, yaitu kebenaran Tuhan. Epistemologi merupakan pandangan filsafat yang menjembatani sumber pengetahuan tertinggi yaitu kebenaran Tuhan. Peran guru Kristen sebagai fasilitator dalam pembelajaran bermakna adalah memfasilitasi siswa untuk mendapatkan pengetahuan tentang Tuhan sehingga kehidupan siswa mengacu pada nilai-nilai Kristiani. Dapat disimpulkan bahwa peran guru Kristen penting dalam mengembangkan pembelajaran yang bermakna bagi siswa agar siswa terus bertumbuh dalam kebenaran Tuhan dan memuliakan Tuhan dalam kehidupannya. Saran untuk peneliti selanjutnya adalah memperdalam tentang penerapan peran guru Kristen sebagai fasilitator dalam mengembangkan pembelajaran yang bermakna melalui observasi langsung dan memperkaya sumber referensi.